Educators' integration of ICT's in teaching mechanics in Grade 10 physical sciences in three approved South African high schools - Mudindo, Fumai Martin (My University, 2016)
This research project reports on the findings of an investigation into ICT (Information and Communication Technology) integration in the teaching of Physical Sciences using the topic of Mechanics as an example. The focus of the research was the effective use of ICT in the teaching and implementation of the curriculum CAPS in the context of teaching the topic of Mechanics. Secondly, to examine the contextual variables those affect the pedagogical integration of ICT in three approved South African high schools. Six teachers from three GDE (a province of influence in South Africa) approved high schools participated voluntarily in this research project. The topic of Mechanics was chosen for this research because learner performance in this topic in the Grade 12 examination has been found to be particularly poor, according to the report of National Senior Certificate Examinations (DBE, 2012). Poor performance in Mechanics might be due to the fact that the concept of energy is highly abstract and probably not well presented by educators starting as far as grade 10 when it commences in CAPS. The research methodology used in this research project was Mixed Methods and a case study as a strategy. A Mixed Methods research design is a procedure for collecting, analysing and integrating both qualitative and quantitative research and methods in a single study to understand a research problem (Creswell, 2012). A case study was motivated by its close connection to the Mixed Methods research design that search for and report complex dynamic and unfolding interactions of events and other factors in unique processes (Cohen, Manion and Morrison, 2011). ICT integration in the Physical Science classroom in teaching complex topic like Mechanics brings about a unique classroom process obviously different from a traditional one. Hence Technological Pedagogical Content Knowledge (TPACK) was used as a theoretical construct that assists in explaining the new science classroom and the teaching dynamics that unfolds in there. Park et al. (2008) studied the effect of ICT in science education on the achievement of Korean middle school students and found a significant difference in the achievement level of the control and experimental class. Livingstone (2012) reported that in the UK a different technology, interactive whiteboards is associated with an improvement in pupils’ performance in national tests in English (particularly for low-achieving pupils and for writing), mathematics and science. TPACK instruments or tools used in this project were the initial questionnaire, an observation schedule, a main questionnaire and a follow-up questionnaire. The responses obtained from these tools were all collected as data and was prepared by coding individual scripts, duplicating and digitizing for ease of safe storage and scoring. The generated scores were then analysed, using the Rasch statistical model. The functionality of the Rasch statistical model was to quantitatively establish the extent of pedagogical and technological use of ICTs in selected educators and the rest of the data was to qualitatively examine the contextual variables that affect the pedagogical integration of ICT. The Rasch statistical model was used to determine the extent of effective use of ICTs for pedagogical and technological use in the teaching of the Grade 10 Physical Sciences topic of Mechanics (research question 1). The findings reveal that the educators were on average at a developing stage in the effective use of ICTs when teaching Mechanics. The specific details of each case are in the research report. The contextual variables that affect the pedagogical integration of ICT in the teaching of Mechanics (research question 2) in these three high schools, according to the participants, include policy or lack of it. The national and provincial policies offers few facts on how educators and schools are expected to incorporate or make use of ICT inside the South African framework. Individual participants had different notions of the purpose of ICT integration. Mr Sibeko was of the notion that ICT integration was for planning efficiency of the whole school. In contrast, Mr Khumo was involved in ICT integration because the MEC or the higher authority had prescribed it. Ms Nomsa was involved because the school obtained ICT through a private sponsor and Mr Ariel just mentioned that ICT integration was “recommended” in the school. The revelations from the findings were important in that the TPACK rubric adapted provided measures that can be quantified and thus allowing the extent of TPACK to be statistically determined (using the Rasch Statistical Model) to a certain degree of consistency as measured by the Cronbach Alpha. One was able to determine if the participant was on standard, developing, elementary or inadequate. Furthermore each trait enabling or hindering was determined. This was unique to this study and will enable planners to determine areas where educators require assistance and support in ICT integration. The limitations of the research project are that in the original design I had intended to audiotape an initial (structured) interview and follow-up (unstructured) interview. This could have helped me to categorically capture the decisive moments such as apprehensions, facial expressions, stammering’s and all the necessary registers of the discourse. Most educators were however of the view that they had time constraints. They suggested that the interviews be converted to questionnaires. Therefore the present structure might have created the impression of monotony of successive questionnaires.
A Research Project (Thesis) in partial fulfilment of the requirements for the Degree of Master of Science (Science Education) Marang Centre for Mathematics and Science Education University of the Witwatersrand, South Africa Johannesburg, 31 May 2016
Keywords: Mechanics.; Information technology--Study and teaching (Secondary)--South Africa.; Physical sciences.